2021
DOI: 10.3390/antiox10040574
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Carbonyl Proteins in the Brain of Mouse Model for Methylglyoxal Detoxification Deficits

Abstract: Recent studies have shown that carbonyl stress is a causative factor of schizophrenia, categorized as carbonyl stress-related schizophrenia (CS-SCZ). However, the correlation between carbonyl stress and the pathogenesis of this disease is not well established. In this study, glyoxalase 1(Glo1)-knockout and vitamin B6-deficient mice (KO/VB6 (-) mice), which are susceptible to methylglyoxal (MGO)-induced oxidative damages, were used as a CS-SCZ model to analyze MGO-modified protein and the carbonyl stress status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Methylglyoxal (MGO) is a highly reactive metabolite of glucose metabolism whose levels are increased in type II diabetic patients. It has been shown to accumulate in the brain of mice deficient for glyoxalase 1/vitamin B6 (MGO detoxification system), suggesting that this imbalance is particularly critical for MGO accumulation in the brain [ 17 ]. Studies have shown that the dysfunction of the glyoxalase system is related to several diabetic complications, including macrovascular diseases in humans [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylglyoxal (MGO) is a highly reactive metabolite of glucose metabolism whose levels are increased in type II diabetic patients. It has been shown to accumulate in the brain of mice deficient for glyoxalase 1/vitamin B6 (MGO detoxification system), suggesting that this imbalance is particularly critical for MGO accumulation in the brain [ 17 ]. Studies have shown that the dysfunction of the glyoxalase system is related to several diabetic complications, including macrovascular diseases in humans [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nasal delivery of carnosine 31,62 via a douche of carnosine in solution is an obvious possibility, however one might also consider a carnosine powder, akin to snuff as used years ago; indeed "snorting" carnosine would be medically preferable to the so-called "recreational" powders which apparently do reach the brain. [63][64][65]…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that Glo1 deletion alone is insufficient to increase MG levels in the brain, and MG accumulation in the brain occurs only when another MG detoxification is deficit, such as VB6 deficiency. In fact, we could also confirm the accumulation of MG-H1, an MG-derived AGE, in the brains of KO/VB6(−) mice [ 67 ].…”
Section: Animal Modelsmentioning
confidence: 94%